2013
DOI: 10.1111/apha.12164
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nuclear factor erythroid 2‐related factor 2 (Nrf2) and Nrf‐2‐dependent genes by ischaemic pre‐conditioning and post‐conditioning: new adaptive endogenous protective responses against renal ischaemia/reperfusion injury

Abstract: The renoprotective action of Ipre might include early activation and enhanced expression of Nrf2 gene and its dependent antioxidant genes, HO-1 and NOQ1, as endogenous adaptive renoprotective genes, as well as reduction in TNF-α, IL-1β, ICAM-1 and caspase-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 48 publications
12
42
0
Order By: Relevance
“…In consistency with this concept, the present study demonstrated significant increase in MDA and significant reduction in GSH and superoxide dismutase (SOD) activity in the kidney homogenates of rats exposed to I/R injury. These findings are in accordance to various previous studies that reported decreased endogenous enzymatic and non-enzymatic antioxidant systems in the renal tissue after I/R injury [2,13,34]. The renoprotective effect for rIPC might be due to intensification of the antioxidants system and reduction of lipid peroxidation [35].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In consistency with this concept, the present study demonstrated significant increase in MDA and significant reduction in GSH and superoxide dismutase (SOD) activity in the kidney homogenates of rats exposed to I/R injury. These findings are in accordance to various previous studies that reported decreased endogenous enzymatic and non-enzymatic antioxidant systems in the renal tissue after I/R injury [2,13,34]. The renoprotective effect for rIPC might be due to intensification of the antioxidants system and reduction of lipid peroxidation [35].…”
Section: Discussionsupporting
confidence: 92%
“…Attraction of neutrophils to the post-ischemic tissue is regulated by increase in expression of adhesion molecules such as intracellular cell adhesive molecule (ICAM-1), complement components such as C5a and a number of chemokines such as IL-8 and macrophage inflammatoryprotein-2 (MIP-2) [33]. We reported in previous studies about the upregulation of ICAM-1 in kidney tissues during renal I/R [13]. Enhanced expression of C5a, IL-8, MIP-2 and ICAM-1 facilitate the recruitment and infiltration of circulating leukocytes to the site of injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tissue damage is exacerbated by the initiated inflammatory response after reperfusion and re-oxygenation of the kidney. The complex serial events during IRI include the release of reactive oxygen species (ROS) and pro-inflammatory cytokines and chemokines and lead to the activation of apoptotic pathways, intracellular Ca 2+ accumulation and tubular cell injury (Shokeir et al 2014, Malek & Nematbakhsh 2015. The detoxification of ROS during oxidative stress is essential for recovery of the kidney and is, for instance, regulated by the transcription nuclear factor erythroid 2-related factor (Nrf2) that accumulates in the nucleus and activates the transcription of phase 2 enzyme genes, such as haeme-oxygenase-1, glutathione reductase and glutathione peroxidase.…”
mentioning
confidence: 99%